Representatividade dos sindicatos na concretização dos direitos fundamentais metaindividuais dos trabalhadores: limites jurídicos da atuação sindical sob enfoque da "teoria do discurso" de Jürgen Habermas - Frossard, Lívia Davel (2015)
This paper is the result of scientific research developed at the Graduate Strictu Sensu Faculdade de Direito de Vitoria approaching on Fundamental Rights and Guarantees, research line on constitutional jurisdiction and implementation of fundamental rights and guarantees. The paper aims to analyze, democratic state paradigm of law, and from the discourse theory developed by Jürgen Habermas, the legal limits on union activity for achievement of fundamental rights of workers. Scientific research will seek to answer metaindividual the following problem from the perspective of 'Discourse Theory' by Habermas, what are the legal limits of union activity for achievement of metaindividual fundamental rights of workers? From the use of the dialectical method, and exploratory and bibliographic research, the first part focus on the rise of unionism in some countries and in Brazil, it has been considering the economic, social and political aspect of the unions in Brazil. In the second part, it is being analyzed the possibility of union activity overcome the limits imposed by law, from the theory of discourse. In addition, it has sought to demonstrate the limits of autonomous union activity, these limits arising from lack of external democratization and imposed by legislation rooted in historicist Rancid corporatist model installed in Brazil in Vargas until the present day. The third part analyzes the importance of collective access to justice as concretizing instrument of metaindividual rights of workers, and the concern will be addressed in inserting a new mentality union leaders to make use of collective protection through the existing procedural micro system, to ensure the worker collective access to justice and protection of rights metaindividuias effective and timely manner.